2007
DOI: 10.1158/0008-5472.can-06-4237
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity-Cancer Link: Lessons Learned from a Fatless Mouse

Abstract: Current dogma suggests that the positive correlation between obesity and cancer is driven by white adipose tissue that accompanies obesity, possibly through excess secretion of adipokines. Recent studies in fatless A-Zip/F1 mice, which have undetectable adipokine levels but display accelerated tumor formation, suggest that adipokines are not required for the enhanced tumor development. The A-Zip/F-1 mice are also diabetic and display elevated circulating levels of other factors frequently associated with obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 18 publications
3
69
0
3
Order By: Relevance
“…It should be noted that the paracrine effects are still considered speculative as the data for in vivo is different from cell culture. For example, in the fatless A-Zip/F1 mouse, adipose tissue and adipokines such as leptin, are unavailable for tumor development making insulin resistance and inflammation the main mechanisms accounting for tumor growth and progression (Hursting et al 2007). Although leptin is produced primarily by adipocytes, it can also be secreted by fibroblasts, the principle component of stroma surrounding the tumor.…”
Section: Leptinmentioning
confidence: 99%
“…It should be noted that the paracrine effects are still considered speculative as the data for in vivo is different from cell culture. For example, in the fatless A-Zip/F1 mouse, adipose tissue and adipokines such as leptin, are unavailable for tumor development making insulin resistance and inflammation the main mechanisms accounting for tumor growth and progression (Hursting et al 2007). Although leptin is produced primarily by adipocytes, it can also be secreted by fibroblasts, the principle component of stroma surrounding the tumor.…”
Section: Leptinmentioning
confidence: 99%
“…64,65 Another study found that obesity was positively associated with death due to prostate cancer metastases. 66 Hursting et al 67 2007 now suggested that the observed increase in obesity associated cancers is the result of chronic inflammation that follows obesity. Also SCDs may play a role in cancer development.…”
Section: Role Of Scd1 In the Link Between Obesity And Cancermentioning
confidence: 99%
“…4 The obesity-cancer progression link may be due in part to dysregulated hormones and obesity-induced inflammation. 5,6 Similar to obese men, obese mice fed a high fat diet also results in increased adiposity, circulating growth factors and inflammation when compared with control mice and may contribute to prostate cancer progression. [7][8][9][10] Studies suggest that cancer cells undergo an epithelialmesenchymal-transition (EMT) program at the initiation of invasion, which is a critical process for metastasis.…”
Section: Introductionmentioning
confidence: 99%